2014
DOI: 10.1063/1.4870005
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal electron-heating mode and formation of secondary-energetic electrons in pulsed microwave-frequency atmospheric microplasmas

Abstract: The formation of secondary energetic electrons induced by an abnormal electron-heating mode in pulsed microwave-frequency atmospheric microplasmas was investigated using particle-in-cell simulation. We found that additional high electron heating only occurs during the first period of the ignition phase after the start of a second pulse at sub-millimeter dimensions. During this period, the electrons are unable to follow the abruptly retreating sheath through diffusion alone. Thus, a selfconsistent electric fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 81%
See 1 more Smart Citation
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 81%
“…Furthermore, only occurring at sub-millimeter dimensions, additional high electron heating are found in the pulsed microwave-driven atmospheric plasmas by using particle-in-cell (PIC) simulations, during the first period of the ignition phase after the start of a second pulse. 16 Another important advantage, the temperature of plasma jet plume can be decreased, due to lower average power absorbed in the pulsed microwave discharge. 17 To pay attention on microwave-driven plasma devices, many researches have focused on optimizing the device structure, in order to acquire special plasma composition, plasma size, and more efficient energy absorbed by plasmas.…”
mentioning
confidence: 99%
“…主要有3个课题组: 韩国浦项工业大学的Kwon等 人 [98] 、美国塔夫茨大学的Hopwood等人 [14] 及田纳西 大学的Levko和Raja [96,97] . 粒子模拟的模型尺寸均针对 1 mm以下的微等离子体进行.…”
Section: 一维粒子模拟(1d3v)大气压低功率微波放电的研究unclassified
“…Plasma biomedicine is an innovative and rapidly evolving research field [12], it mainly needs the RF sources to produce the cold atmospheric plasma (CAP) with stability and reactivity in the α mode for different therapeutic settings [13]. However, with the input power further increased, the RF discharge usually suffers from the α − γ mode transition accompanied by the remarkable power consumption and high gas temperature as the current density enhanced [14]- [20], which greatly limits the application of atmospheric RF plasma to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when the pulse modulation is introduced into microplasmas maintained by the dielectric barrier discharges (DBDs) with the driving frequency in the range of UHF, LDCs will also occur in the first positive and negative half-cycle during the power-on phase, respectively [42]- [44]. Detailed computational results by particle-in-cell/Monte Carlo collision (PIC-MCC) model have illustrated that quantities of energetic electrons larger than 50 eV can also be generated in an effective way [45]- [47], which are supposed to be crucial to break chemical bonds in the plasma biomedicine applications [20], [42], [48], [49]. In this study, it is proposed that the underpinning physics of the production of LDCs in two types of discharge structures, especially their distinctive sheath structure may be helpful to further understand the corresponding discharge mechanisms and find the methods for optimizing the LDCs for plasma applications at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%